Mobile genetic elements of Staphylococcus aureus - Malachowa, Natalia (SP Birkhäuser Verlag Basel, 2010)
Bacteria such as Staphylococcus aureus are successful as commensal organisms or pathogens in part because they adapt rapidly to selective pressures imparted by the human host. Mobile genetic elements (MGEs) play a central role in this adaptation process and are a means to transfer genetic information (DNA) among and within bacterial species. Importantly, MGEs encode putative virulence factors and molecules that confer resistance to antibiotics, including the gene that confers resistance to beta-lactam antibiotics in methicillin-resistant S. aureus (MRSA). Inasmuch as MRSA infections are a significant problem worldwide and continue to emerge in epidemic waves, there has been significant effort to improve diagnostic assays and to develop new antimicrobial agents for treatment of disease. Our understanding of S. aureus MGEs and the molecules they encode has played an important role toward these ends and has provided detailed insight into the evolution of antimicrobial resistance mechanisms and virulence.